Two-year prognostic value of mean platelet volume in patients with diabetes and stable coronary artery disease undergoing elective percutaneous coronary intervention - Jiang, Ping (Cardiol J, 2019)
BACKGROUND: Mean platelet volume (MPV) is a marker of platelet size and activity, and is associated with a poor prognosis of cardiovascular disease. Studies have shown a relationship between diabetes mellitus (DM) and MPV. This study examined the relationship between admission MPV and 2-year cardiac mortality in patients with DM and stable coronary artery disease (SCAD) undergoing elective percutaneous coronary intervention (PCI). METHODS: A total of 1389 patients were enrolled and divided into two groups according to MPV as follows: lower MPV (n = 908, MPV ≤ 10.9 fL) and higher MPV (n = 481, MPV > 10.9 fL). RESULTS: Body mass index, platelet distribution width, MPV/platelet and glycated hemoglobin (HbA1c) levels were significantly higher in the higher MPV group compared with the lower MPV group (all p < 0.05). The platelet count was significantly lower in the higher MPV group compared with the lower MPV group (p < 0.05). MPV was positively associated with HbA1c and fasting plasma glucose levels (r = 0.073 and 0.061, p = 0.007 and 0.023, respectively) in bivariate correlation analysis. The 2-year cardiac mortality rate was 0.7%, and was significantly lower in the lower MPV group than in the higher MPV group in Kaplan-Meier analysis (p = 0.019). Receiver operating characteristic analysis showed a good diagnostic value for MPV at predicting long-term cardiac mortality (area under the curve: 0.735, 95% confidence interval [CI]: 0.590–0.880, p = 0.01). Elevated MPV was a significant risk factor for 2-year cardiac mortality (hazard ratio: 2.091, 95% CI: 1.075–4.070, p = 0.030) in multivariable Cox regression analysis. CONCLUSIONS: Mean platelet volume is a strong, independent prognostic factor in PCI-treated patients with DM and SCAD.